STIMULASI AL-QUR’AN DALAM MENINGKATKAN IMUNITAS SPIRITUAL PERSEPEKTIF QS. AR-RA’D: 28 - Shodiq Ahmad, Mohammad; Noor, Ali Fikri; Darsih (Darul Hikmah: Jurnal Penelitian Tafsir dan Hadits, 2021)
Various mental illnesses appear and increase from year to year, even more so with the test of the Covid-19 outbreak which never ends. This certainly has an impact on society, both in terms of economic, health, social and so on, and especially on the psychological side. The number of problems that arise, causing a variety of stress (multiple stressors) in society. It is feared that it will trigger increased anxiety and depression in society.This study aims to determine remembrance as a stimulant that can increase spiritual immunity in the form of peace of mind. It is also a preventive tool for preventing mental disorders (heart) caused by life's problems, by inviting back to the Qur'an and Sunnah as a guide to the life of a Muslim. This is the Qur'an that guides to the truth with all His care and care. By using the literature study research method, the author analyzes the study of the interpretation of Qs. Ar-Ra'd verse 28 from various points of view of the commentators, both classical and contemporary, with a focus on the study that remembrance is a stimulus to gain spiritual immunity in the form of peace of mind. The results of the research analysis show that by always remembering Allah SWT, both by interacting with the Qur'an and establishing prayers, it will increase spiritual immunity. An indicator of increasing spiritual immunity is the presence of peace of mind. The more the quality of remembrance increases, the more the quality of peace of mind increases. And this is one of the preventive medicines from the Qur'an to prevent the birth of mental illness in the form of anxiety and depression, where many of its emergence begins with the seeds of heart disease such as hasad, envy, emotion, riya, stubbornness, and others.